Detection and quantification of key dental pathogens through wastewater monitoring - Olivia N. Birch; Sang C. Par; Justin C. Greaves (PLoS ONE, 2025)
Wastewater-based epidemiology (WBE) has been widely used to track viral pathogens like SARS-CoV-2 and polio, but its potential for monitoring common dental bacterial pathogens that infect the oral cavity has yet to be explored. Streptococcus mutans and Porphyromonas gingivalis are key oral bacterial pathogens that cause highly prevalent dental diseases worldwide, such as dental caries and gingivitis. Our main objective for this study was to investigate the presence and prevalence of these oral bacteria in wastewater to determine the feasibility of using WBE for oral pathogens. We measured S. mutans and P. gingivalis nucleic acids in weekly samples for 24 months at a local wastewater treatment plant. Between June 2023 and May 2025, a weekly sample of untreated wastewater was collected, resulting in a total of 100 samples collected over the timespan. Samples were concentrated, extracted for DNA, and then tested for each bacterium. Our results showed that 89% and 58% were positive for S. mutans and P. gingivalis , respectively, which shows that wastewater surveillance is appropriate for oral bacteria. Average concentrations were 4.57 log 10 genome copies/L and 3.03 log 10 genome copies/L for S. mutans and P. gingivalis , respectively. Detections of oral bacteria were observed in the primary and final effluent, but concentrations were significantly lower in the final effluent than in the untreated wastewater. The high levels of oral bacteria in wastewater indicated a potential transmission mechanism for these bacteria through water, specifically for S. mutans . Additionally, this study underscores the unique potential for WBE to be used in the surveillance of oral bacterial pathogens.